A Multifactor Approach to Mild Cognitive Impairment - Qarni, Taha; Salardini, Arash (Seminars in Neurology, 2019)
Mild cognitive impairment (MCI) represents an intermediate stage between normal cognition and dementia. Individuals with MCI are at increased risk of conversion to dementia, and the rate of progression of MCI to dementia is dependent on age, gender, and education. MCI may be diagnosed using neuropsychological criteria using cut-offs representing decrements in cognition, or using criteria to assess for a decline in functional status. The ability to determine the status of dementia-related biomarkers has allowed for better staging and prognostication in different forms of MCI. MCI is now recognized as a significant target stage for future therapies. These future therapies aim to reduce the rate of conversion of individuals with MCI to dementia. In this article, we review different conceptions of MCI, the diagnosis and prognostication of MCI, and presently available management approaches for this condition.
Keywords: mild cognitive impairment; MCI; dementia